(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effectiveness of vaginal Misoprostol for the second trimester termination of pregnancy. Study Design: Prospective randomized trial. Place & Duration of Study: This study was carried out in the Unit of Post Graduate Medical Institution Peshawar / Lady Reading Hospital Peshawar from 1st January till 31st December 2006. Materials and Methods: A total of 100 patients were included in this study. Misoprostol 400 microgram, was administered intra-vaginally and repeated after every 4 hours up to a maximum of five doses or until the termination of pregnancy, which ever was earlier. The exclusion criteria were as allergy to prostaglandin, a previous classic caesarean section or Hysterectomy, active vaginal bleeding, severe asthma and epilepsy. Results: Period of gestation ranged from 12 to 20 weeks. Indications for 2nd trimester termination of pregnancy were chromosomal or structural fetal anomalies (anencephaly) whether dead or alive, missed abortion intrauterine fetal death. Success rate at 48 hours was 90%. The median induction to termination interval was 16 hours. Few women suffered gastrointestinal side effects such as nausea (6%), vomiting (3%) and diarrhea (1%). Conclusion: 400 Microgram of Vaginal Misoprostol is highly effective way of cervical ripening and termination of second trimester pregnancy.